Pengaruh Motivasi Investasi, Risk Perception, dan Loss Aversion terhadap Keputusan Investasi Generasi Z Bandung yang Dimoderasi oleh Financial Literacy - Ratna Nabilah Hayati; Desmiza Desmiza (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
The growth in the number of investors in the Indonesian capital market has increased every year, but the increase in investors is not accompanied by an increase in Asset Under Management (AUM). This study was conducted to examine the effect of investment motivation, risk perception, and loss aversion on investment decisions moderated by financial literacy. This research is an associative descriptive research with a quantitative approach. The population of this study is generation Z Bandung investors with sampling using non probability sampling techniques resulting in a sample size of 160 respondents. Respondent data using a questionnaire distributed via google form. The data analysis technique uses multiple linear regression involving Moderated Regression Analysis (MRA). The results of this study indicate that investment motivation and loss aversion have a positive effect on investment decisions while risk perception has a negative effect on investment decisions, and financial literacy can moderate the effect of investment motivation, risk perception, and loss aversion on investment decisions.   Keywords: Investment Motivation, Risk Perception, Loss Aversion, Investment Decision, Financial Literacy